Carboxylated phytosterol derivative-introduced liposomes for skin environment-responsive transdermal drug delivery system. (2nd October 2018) - Yamazaki, Naoko; Yamakawa, Satoshi; Sugimoto, Takumi; Yoshizaki, Yuta; Teranishi, Ryoma; Hayashi, Takaaki; Kotaka, Aki; Shinde, Chiharu; Kumei, Takayuki; Sumida, Yasushi; Shimizu, Toru; Ohashi, Yukihiro; et al.
Abstract: Transdermal drug delivery systems are a key technology for skin-related diseases and for cosmetics development. The delivery of active ingredients to an appropriate site or target cells can greatly improve the efficacy of medical and cosmetic agents. For this study, liposome-based transdermal delivery systems were developed using pH-responsive phytosterol derivatives as liposome components. Succinylated phytosterol (Suc-PS) and 2-carboxy-cyclohexane-1-carboxylated phytosterol (CHex-PS) were synthesized by esterification of hydroxy groups of phytosterol. Modification of phytosterol derivatives on 1, 2-dimyristoyl- sn -glycero-3-phosphocholine (DMPC) liposomes was confirmed by negatively zeta potentials at alkaline pH and the change of zeta potentials with decreasing pH. In response to acidic pH and temperatures higher than body temperature, Suc-PS-containing and CHex-PS-containing liposomes exhibited content release at intracellular acidic compartments of the melanocytes at the basement membrane of the skin. Phytosterol-derivative-containing liposomes were taken up by murine melanoma-derived B16-F10 cells. These liposomes delivered their contents into endosomes and cytosol of B16-F10 cells. Furthermore, phytosterol-derivative-containing liposomes penetrated the 3 D skin models and reached the basement membrane. Results show that pH-responsive phytosterol-derivative-containing DMPC liposomes are promising for use in transdermal medical or cosmetic agent delivery to melanocytes.